2008
DOI: 10.1093/europace/eun085
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes in patients with atrioventricular block undergoing septal ventricular lead implantation compared with standard apical pacing

Abstract: With regard to different parameters of congestive heart failure, a septal stimulation site is not superior to conventional apical pacing in unselected patients undergoing pacemaker implantation for AV-block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 29 publications
1
79
0
3
Order By: Relevance
“…The RV septal pacing also resulted in shorter isovolumic relaxation than RV apical pacing (Yu et al, 2007), implicating better diastolic function that has been invasively demonstrated by Kolettis et al (Kolettis et al, 2000) at the cardiac catheterization laboratory. In fact despite the beneficial features of reducing electrical and mechanical dyssynchrony , different studies failed to demonstrate a positive effect on indices of LV structure and 85 function and did not confirm the above mentioned clinical outcomes, at least during the 3-18 months after implantation (Bourke et al, 2002;Victor et al, 2006;Kypta et al, 2008;Dabrowska-Kugacka et al, 2009;Gong et al, 2009;Cano et al, 2010) Kypta et al (Kypta et al, 2008) randomized 98 patients with atrioventricular block (AVblock) undergoing pacemaker implantation to positioning the ventricular lead in the high or mid septum (n =53) or in the apex (n = 45) of the right ventricle. The Changes of N-terminal pro-brain natriuetic peptide (BNP) levels, LVEF, and exercise capacity from baseline to 18 months were statistically not different between septal and apical stimulation.…”
Section: Authorsmentioning
confidence: 99%
See 4 more Smart Citations
“…The RV septal pacing also resulted in shorter isovolumic relaxation than RV apical pacing (Yu et al, 2007), implicating better diastolic function that has been invasively demonstrated by Kolettis et al (Kolettis et al, 2000) at the cardiac catheterization laboratory. In fact despite the beneficial features of reducing electrical and mechanical dyssynchrony , different studies failed to demonstrate a positive effect on indices of LV structure and 85 function and did not confirm the above mentioned clinical outcomes, at least during the 3-18 months after implantation (Bourke et al, 2002;Victor et al, 2006;Kypta et al, 2008;Dabrowska-Kugacka et al, 2009;Gong et al, 2009;Cano et al, 2010) Kypta et al (Kypta et al, 2008) randomized 98 patients with atrioventricular block (AVblock) undergoing pacemaker implantation to positioning the ventricular lead in the high or mid septum (n =53) or in the apex (n = 45) of the right ventricle. The Changes of N-terminal pro-brain natriuetic peptide (BNP) levels, LVEF, and exercise capacity from baseline to 18 months were statistically not different between septal and apical stimulation.…”
Section: Authorsmentioning
confidence: 99%
“…Right Ventricular Apical permanent pacing could have negative hemodynamic effects. Initially, attention was directed to RV outflow tract/septum pacing and His/para-Hisian pacing in patients with LV dysfunction ( Mera et al, 1999;Schwaab et al, 1999;Buckingham et al, 1997;Buckingham et al, 1998;de Cock et al, 1998) and latter in preserved LV function patients (Giudici et al, 1997;Karpawich & Mital, 1997;Kolettis et al, 2000;Bourke et al, 2002;Tse et al, 2002;Occhetta et al, 2006;Victor et al, 2006;Yu et al, 2007;Kypta et al, 2008;Flevari et al, 2009;Ng et al, 2009;Dabrowska-Kugacka et al, 2009;Takemoto et al, 2009;Gong et al, 2009;Rosso et al, 2010;Verma et al , 2010;106:806-9;Leong et al, 2010;Cano et al,. 2010;Yoshikawa et al, 2010) while subsequently biventricular stimulation began to emerge as an appealing alternative proposal (Yu et al, 2009;Simantirakis et al, 2009;Doshi et al, 2005).…”
Section: Pacing Site Selectionmentioning
confidence: 99%
See 3 more Smart Citations